The opioid use disorder core outcomes set (OUD–COS) for treatment research: findings from a Delphi consensus study. (25th April 2022) - Karnik, Niranjan S.; Marsden, John; McCluskey, Connor; Boley, Randy A.; Bradley, Katharine A.; Campbell, Cynthia I.; Curtis, Megan E.; Fiellin, David; Ghitza, Udi; Hefner, Kathryn; Hser, Yih‐Ing; McHugh, R. Kathryn; et al.
Abstract: Background and Aim: There is no gold‐standard and considerable heterogeneity in outcome measures used to evaluate treatments for opioid use disorder (OUD) along the opioid treatment cascade. The aim of this study was to develop the US National Institute on Drug Abuse (NIDA) National Drug Abuse Treatment Clinical Trials Network (CTN) opioid use disorder core outcomes set (OUD–COS). Design: Four‐round, e‐Delphi expert panel consensus study and plenary research group discussion and targeted consultation. Setting: United States. Participants: A panel of 25 members including clinical practitioners, clinical researchers and administrative staff from the CTN, the network's affiliated clinical and community sites and the NIDA Centre for the CTN. Measurements: From a pool of 24 candidate items in four domains (biomedical/disease status; behaviors, symptoms and functioning; opioid treatment cascade; and morbidity and mortality), the panel completed an on‐line questionnaire to rank items with defined specification on a 9‐point scale for importance, with a standard 70% consensus criterion. Findings: After the fourth round of the questionnaire and subsequent discussion, consensus was reached for five outcomes: two patient‐reported (global impression of improvement and incident non‐fatal overdose); one clinician‐reported (illicit/non‐medical drug toxicology); and two from administrative records (duration of treatment and fatal opioid poisoning). Conclusions: An e‐Delphi consensus study has produced the US National Institute on Drug Abuse (NIDA) National Drug Abuse Treatment Clinical Trials Network opioid use disorder core outcomes set (version 1) for opioid use disorder treatment efficacy and effectiveness research.